2006
DOI: 10.1590/s0100-84042006000400018
|View full text |Cite
|
Sign up to set email alerts
|

Composição química do sedimento e de folhas das espécies do manguezal do estuário do Rio São Mateus, Espírito Santo, Brasil

Abstract: -(Chemical composition of sediments and leaves of mangrove species at the São Mateus river estuary, Espírito Santo State, Brazil). We analyzed nutrient concentrations in leaves and sediments, and element accumulation capacity in foliar tissues of Avicennia germinans (L.) Stearn., Avicennia schaueriana Staft & Leechm., Laguncularia racemosa (L.) Gaertn. f. and Rhizophora mangle L. in four sites along the São Mateus River estuary mangrove, Espírito Santo State, SE-Brazil. In sediment, elements decrease following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 23 publications
3
39
1
16
Order By: Relevance
“…Average values of leaf concentrations were consistent with the values described in the literature on Brazilian mangroves Bernini and Rezende 2010;Cuzzuol and Rocha 2012). The variation in the leaf concentrations observed among the studied species (Table 3) was partly due to the salt excluding condition of the Rhizophora gender species, or to the salt including condition of the Avicennia and Avicennia gender species (Lacerda et al 1985;Bernini et al 2006). Specifically, the low leaf levels of Fe, Zn and Cu in R mangle could be due to the salt exclusion mechanism, which affected the absorption of these elements (Lacerda et al 1985).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Average values of leaf concentrations were consistent with the values described in the literature on Brazilian mangroves Bernini and Rezende 2010;Cuzzuol and Rocha 2012). The variation in the leaf concentrations observed among the studied species (Table 3) was partly due to the salt excluding condition of the Rhizophora gender species, or to the salt including condition of the Avicennia and Avicennia gender species (Lacerda et al 1985;Bernini et al 2006). Specifically, the low leaf levels of Fe, Zn and Cu in R mangle could be due to the salt exclusion mechanism, which affected the absorption of these elements (Lacerda et al 1985).…”
Section: Discussionsupporting
confidence: 88%
“…In the studied areas, the differences in Fe, Mn, Cu, and Zn concentrations in the soils, both between the species and mangroves could be related to temporal (Cuzzuol and Rocha 2012) and spatial variations, which were linked to the chemical and physical characteristics of the soil (Bernini et al 2006;. Tides variation also interfered on the availability of chemical elements (Lacerda et al 1986), resulting in a concentration/dilution effect on the nutrients of this ecosystem (Ong Che 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N and P concentrations are within the upper range of variation in mangroves elsewhere indicating that the sediments in these mangrove sites are quite fertile as suggested also by the soil analyses (Lacerda et al, 1985;Medina et al, 2001;Bernini et al, 2006;Lugo et al, 2007;Medina et al, 2010). Besides, the N/P molar ratios are all below 30 for the mangrove species, and slightly above 30 in the associated species, well below the values reported from P-limited mangroves in the Caribbean .…”
Section: Plantssupporting
confidence: 57%
“…These cations sequences have a wide range of variations among mangroves that are associated with the influence of marine waters. In São Matheus, Brasil (≈18ºS) Bernini et al (2006) reported K concentrations in sediments of 5.9 mmol kg -1 , well below the values obtained in our sites in Santa Catarina, and the cation sequence was Mg>Ca>K. In Bragança peninsula (Para, Brasil, ≈1ºS) K concentrations decreased towards to coast but were always higher than Ca concentrations (Medina et al 2001) The average Na/K molar ratios are larger for PA (18), followed by TA (7) and LA (2), differing markedly from the Na/K ratio of standard sea water (46). This indicates that all three sites are within a humid climate zone, rainfall counteracting Na accumulation in the superficial soil layer.…”
Section: Soilsmentioning
confidence: 99%